اثر اسلوب التنافس المقارن فى تعليم بعض المهارات الاساسية بكرة القدم لطلاب الصف الرابع الاعدادى - بطرس، آمال نورى; بكر، مسلم جعفر جمعة (جامعة الموصل - كلية التربية الأساسية, 2012)
هدفت الدراسة إلى الكشف عن: \ - أثر أسلوب (التنافس المقارن) في تعليم بعض المهارات الأساسية بكرة القدم لطلاب الصف الرابع الإعدادي. \ - المقارنة في الاختبار البعدي بين أسلوبي (التنافس المقارن والإمري) في تعليم بعض المهارات الأساسية بكرة القدم لطلاب الصف الرابع الإعدادي. \ وافترض الباحثان ما يأتي: - \ -\ وجود فروق ذي دلالة إحصائية في متوسط درجات الطلاب بين الاختيارين القبلي والبعدي لمجموعتي البحث في تعليم بعض المهارات الأساسية بكرة القدم لصالح الاختبار الابعدي. \ -\ وجود فروق ذي دلالة إحصائية في متوسط درجات الطلاب في الاختبار البعدي بين مجموعتي البحث في بعض المهارات الأساسية بكرة القدم لصالح الاختبار الابعدي. \ واستخدم الباحثان المنهج التجريبي لملاءمته وطبيعة البحث، وتكونت عينة البحث من طلاب الصف الرابع الإعدادي في إعدادية الكندي للبنين في مدينة الموصل للعام الدراسي (2009-2010) البالغ عددهم (40) طالبا. وتم تطبيق كل أسلوب من الأساليب المستخدمة على كل مجموعة لتعليم بعض المهارات الأساسية بكرة القدم على وفق الآتي: \ - المجموعة التجريبية........... أسلوب التنافس المقارن. \ - المجموعة الضابطة........... أسلوب الأمري. \ وتم تحقيق التكافؤ لمجموعتي البحث في متغيرات (العمر والكتلة والطول) وبعض عناصر اللياقة البدنية المؤثرة في تعليم بعض المهارات الأساسية في كرة القدم. \ وتم البدء بتنفيذ التجربة الرئيسة يوم الأحد الموافق (21-2-2010) وانتهت يوم الأربعاء (14-4-2010) \ وتم التوصل إلي الاستنتاجات الإتية. \ 1- إن أسلوبي (التنافس المقارن والامري) هما أسلوبان فعالان في تعليم مستوى الأداء للمهارات (الدحرجة والمناولة القصيرة والمتوسطة والطويلة والتهديف القريب والبعيد والإخماد وضرب الكرة بالرأس) في كرة القدم بنسب مختلفة. \ 2- تفوق أسلوب التنافس المقارن في تعليم مهارات (الدحرجة والتمريرة القصيرة والمتوسطة والطويلة والتهديف القريب والبعيد و الإخماد وضرب الكرة بالرأس) في كرة القدم على أسلوب الأمري. \ وأوصى الباحثان بما يأتي: \ 1- استخدام أسلوب (التنافس المقارن) في تعليم بعض المهارات الأساسية بكرة القدم (الدحرجة والمناولة القصيرة والمتوسطة والطويلة والتهديف القريب والبعيد والإخماد وضرب الكرة بالرأس) على طلاب الرابع الإعدادي. \ 2- ضرورة اهتمام مدرسي التربية في المدارس باستخدام أسلوب التنافس المقارن في تعليم بعض المهارات الأساسية بكرة القدم. \ واقترح الباحثان: \ 1- إجراء دراسات لأسلوب التنافس المقارن على مراحل دراسية أخرى من البنين لاعبة كرة القدم. \ 2- إجراء دراسات أخرى لأسلوب التنافس المقارن على مراحل دراسية أخرى من البنين والبنات لألعاب رياضية مختلفة. The current study aims at: \ - Revealing the impact of using comparative competition style in \ teaching some of the basic skills in football for fourth class secondary school pupils. \ - Comparing post tests of both (comparative competition and \ Commanding) styles in teaching some basic skills of football for fourth secondary school students. \ The researcher has hypothesized the following: \ - There are statistically significant differences in the grades of the pupils between pre and post tests for the study groups in teaching some basic skills of football and in favor of the post test. \ - There are statistically significant differences in averages of students in post test for the study groups in some basic skills of football and in favor of the experimental group . \ Experimental approach is used for its suitability to the study \ approach. The study sample consisted of (40) fourth secondary stage students at Al Kindi School for Boys in the city of Mosul for the year academic (2009 2010). \ Each of the methods developed by the researchers was applied to teaching some of the basic skills of football as follows: \ - first experimental group: comparative competition method. \ - Control group: Commanding style. \ Equivalence has been achieved for the three groups regarding age, weight and height and some of the physical fitness affecting the \ development of basic skills in football. \ The main experiment started on Sunday 21 st February 2010 and finished on Wednesday 14th March 2010. \ The study sums up with the following: \ 1. The comparative competition and Commanding style, are efficient in teaching the basic skills (rolling, short, medium and long pass, close and distant shooting, hitting the ball with head) in football with various rates. \ 2. Comparative method is better than the Commanding methods in teaching some of the basic skills in football (rolling, short, medium and long pass, close and distant shooting, hitting the ball with head) The researcher has recommended the following: \ 1. Using comparative style in teaching some of the basic skills in football (rolling, short, medium and long pass, close and distant shooting, hitting the ball with the head) for the fourth secondary stage students. \ 2. Paying more attention by physical sport teachers to use comparative method in teaching and maintaining some of the basic skills of football. \ The following are suggested by the researcher: \ 1. conducting other studies using comparative competition method for other teaching stages for boys in football. \ 2. Making other studies using comparative competition method for other teaching stages for boys and girls in various games.
Keywords: طرق التدريس -- التعليم المتوسط -- طلاب المدارس الاعدادية -- تدريس التربية الرياضية -- الالعاب الرياضية -- كرة القدم -- المهارات الرياضية -- العراق